Pemetaan Spasial serta Studi Korelasi antara Faktor Demografi, Lingkungan, dan Kasus Tuberkulosis di Kota Bogor Tahun 2023 - Fadhlillah, Muhammad Imam; Buntara, Arga; Fithri, Nayla Kamilia; Simanjorang, Chandrayani (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: The city of Bogor has recorded a steady increase in the number of TB cases over the past three years, reaching 6,142 cases in 2023 with the highest treatment-related mortality rate in West Java (270 deaths). This study aims to analyze the relationship between demographic and environmental factors and TB incidence, as well as analyze the spatial distribution of use in the city of Bogor in 2023.Methods: The study employed an ecological design based on administrative areas, with six districts as units of analysis: Bogor Barat, Bogor Timur, Bogor Tengah, Bogor Selatan, Bogor Utara, and Tanah Sareal. Secondary data were obtained from the Bogor City Health Office (TB case data by age and sex, 2023), Statistics Indonesia (BPS) of Bogor City (population density and housing density, 2023), and the Bogor Class II Meteorological Station (BMKG) (average air temperature and humidity, 2023). Spatial analysis was conducted using QGIS and bivariate analysis using Pearson correlation.Result: A total of 6,142 TB cases were recorded in 2023. The highest number was in Bogor Barat (1,419 cases), followed by Bogor Selatan (1,320) and Tanah Sareal (1,147), while the lowest was in Bogor Timur (539 cases). Spatial mapping showed higher case concentrations in the western and southern parts of the city. The sex variable (male r = 0.880, female r = 0.901) showed a strong correlation with TB cases.Conclusion : This study recommends targeted TB interventions in high-burden areas and consideration of demographic aspects as risk indicators.